(untitled) (Open Academia: Journal of Scholarly Research, 2025)
The article provides information about the concept of maqasid ash-shari’a (goals of the Shari’a) in Islamic law, its structure, and working mechanisms. Also, the stages of formation of this concept as an auxiliary science in Islamic law are highlighted.